2018
DOI: 10.14719/pst.2018.5.2.365
|View full text |Cite
|
Sign up to set email alerts
|

An ethnobotanical study of plants used by forest fringe communities of Lwali village (Pauri Garhwal, Uttarakhand)

Abstract: The paper provides information on traditional knowledge of plants used by fringe forest communities of village Lwali (District Pauri Garhwal). The paper deals with 35 plant species belonging to 34 genera of 29 families, that find mention in the local folklore. The plants have been provided with botanical names, vernacular names, parts used and ethnobotanical uses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
1
1
0
Order By: Relevance
“…The study confirmed the uses of 125 plant species that are being used for various purposes in the form of wild edible. The results of the present study are although in conformity with the reports of previous studies, on different tribes of north eastern region (13,35,36,37) as well as other Indian states (3,14,15), the number of species reported here is comparatively higher. Uses of about 195 plant species as wild edible by the tribal communities from Indian Himalayan region have also been reported in the previous studies (32).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The study confirmed the uses of 125 plant species that are being used for various purposes in the form of wild edible. The results of the present study are although in conformity with the reports of previous studies, on different tribes of north eastern region (13,35,36,37) as well as other Indian states (3,14,15), the number of species reported here is comparatively higher. Uses of about 195 plant species as wild edible by the tribal communities from Indian Himalayan region have also been reported in the previous studies (32).…”
Section: Discussionsupporting
confidence: 93%
“…These studies highlighted the selection of promising species for domestication for dietary alternatives and to meet the nutritional requirement of the large population. India is known for its rich floristic and cultural diversity where a large number of plant species are consumed by the rural communities, forming an integral part of the food and dietary requirements (13)(14)(15)(16).…”
Section: Introductionmentioning
confidence: 99%